(untitled) (Eurasian Medical Research Periodical, 2022)
For the intensive treatment of purulent inflammation of the fingers and hooves in cattle of Simmental breed, effective treatment of intravenous and enrofloxacin 10% antibiotic with intravenous and butasal-100 + sodium chloride 0.9% solution + ascorbic acid, which acts as a bio-stimulant method was developed and treatment duration was reduced to 7 days compared to the control group